Collection Development in a Resource Sharing Environment - Alvi, Wajih A. (DESIDOC Journal of Library & Information Technology, 2003)
This article briefly explains the changing phase of collection development while discussing the information explosion in recent years along with an example of Chemical Abstracts for the same. It puts emphasis on co operative collection development policies suited to the current philosophy of providing access to information through a sharing mechanism, stresses upon the need of improving the quality of library services through it, and also discusses its advantages. http://dx.doi.org/10.14429/dbit.17.2.3327